A comparison of static and dynamic ∆B0 mapping methods for correction of CEST MRI in the presence of temporal B0 field variations. Issue 2 (28th March 2019) - Poblador Rodriguez, Esau; Moser, Philipp; Dymerska, Barbara; Robinson, Simon; Schmitt, Benjamin; van der Kouwe, Andre; Gruber, Stephan; Trattnig, Siegfried; Bogner, Wolfgang
Abstract : Purpose: To assess the performance, in the presence of scanner instabilities, of three dynamic correction methods which integrate ∆ B 0 mapping into the chemical exchange saturation transfer (CEST) measurement and three established static ∆ B 0 ‐correction approaches. Methods: A homogeneous phantom and five healthy volunteers were scanned with a CEST sequence at 7 T. The in vivo measurements were performed twice: first with unaltered system frequency and again applying frequency shifts during the CEST acquisition. In all cases, retrospective voxel‐wise ∆ B 0 ‐correction was performed using one intrinsic and two extrinsic [prescans with dual‐echo gradient‐echo and water saturation shift referencing (WASSR)] static approaches. These were compared with two intrinsic [using phase data directly generated by single‐echo or double‐echo GRE (gradient‐echo) CEST readout (CEST‐GRE‐2TE)] and one extrinsic [phase from interleaved dual‐echo EPI (echo planar imaging) navigator (NAV‐EPI‐2TE)] dynamic ∆ B 0 ‐correction approaches [allowing correction of each Z‐spectral point before magnetization transfer ratio asymmetry ( MTRasym ) analysis]. Results: All three dynamic methods successfully mapped the induced drift. The intrinsic approaches were affected by the CEST labeling near water (∆ ω < |0.3| ppm). The MTRasym contrast was distorted by the frequency drift in the brain by up to 0.21%/Hz when static ∆ B 0 ‐corrections were applied, whereas the dynamic ∆ B 0 corrections reduced this to <0.01%/Hz without the need of external scans. The CEST‐GRE‐2TE and NAV‐EPI‐2TE resulted in highly consistent MTRasym values with/without drift for all subjects. Conclusion: Reliable correction of scanner instabilities is essential to establish clinical CEST MRI. The three dynamic approaches presented improved the ∆ B 0 ‐correction performance significantly in the presence of frequency drift compared to established static methods. Among them, the self‐corrected CEST‐GRE‐2TE was the most accurate and straightforward to implement.